PENGARUH RELATIONSHIP MARKETING DAN KEUNGGULAN PRODUK TERHADAP KESETIAAN NASABAH PADA PT.BANK SYARIAH MANDIRI CABANG BANDA ACEH - Yuliana Yuliana; Edwar M Nur; Reza Juanda; Sri Wahyu Yusni (Departemen Manajemen, Universitas Syiah Kuala, 2018)
The purpose of this study was to determine the effect of Relationship Marketing on Customer’s loyalty at PT. Bank Syariah Mandiri Banda Aceh Branch as well as simultaneously determine the effect of Relationship Marketing and Product Excellence on Costumer’s loyalty at PT. Bank Syariah Mandiri Banda Aceh Branch. This study was conducted at PT. Bank Syariah Mandiri Banda Aceh Branch which is located on Jalan Dipenogoro Banda Aceh. Then total subject of tis study was 150 respondents. The data that has fulfilled the test of validity, reliability and classical test are then processed so that the regression equation resulted as follows: Y = 2.020 + 0.185x1 + 0.177X2 + eThe result of the study showed that the relation between customer’s loyalty and product excellence altogether have a significant effect on customer’s loyalty at PT. Bank Syariah Mandiri Banda Aceh Branch with obtained Fcount of 23,361, while F table at a significant level of α = 5% was 2,666, then the result of this study also proved that individual client has a significant effect on customer’s loyalty at PT. Bank Syariah Mandiri Banda Branch Aceh with a regression coefficient of 0.185. The result of the study also proved that the superiority of the products provided by PT. Bank Syariah Mandiri Banda Aceh Branch individually has a significant effect on customer’s loyalty at PT. Bank Syariah Mandiri Banda Aceh Branch with a regression coefficient of 0.177. After conducting this research, PT. Bank Syariah Mandiri Banda Aceh Branch is very popular amongst the society, therefore it should have been able to improve their services to customers, so that customers become satisfied with the provided services. KeywordsRelationship Marketing, Product Excellence and Customer Loyalty